ترجمة القصة القصيرة "رجل وخمس نساء" لعبد الله ناصر الداوود بطريقة التحليل لمونا بيكر ومشكلاتها - Cahya Edi Setyawan; Ahmad Taufik; Zakiyah Rosalina (LISANIA: Journal of Arabic Education and Literature, 2017)
This paper aims to analyze the translation of short story "Rajulun wa Khamsu Nisâ`" written by Abdullah Naseer Ad-Dawud. This study focuses on the problem of idiomatic expressions translation. The idiom is an expression consisting of two or more words which have different meaning from its conjunctive word construction, so it must be understood in context and translated by looking at its equivalent to the target language. The purpose of this study is to know how to get the short story translation results correctly. The method used in this research is descriptive analysis method, it done by presenting the data, then analyze it systematically so it can be more easily to understood. Data analysis methods used in this research is an idiom analysis that refers to the idiom translation strategies in the “In Other word”, a book by Mona Baker. This idioms translation strategies are using similar meaning and form, using similar meaning but dissimilar form, translation by pharaphrase, and omission. The results in this research are four idiom patterns forms in the story of Rajulun wa Khamsu Nisaa, which are named as al-jumlah, al-idlafi, af'al al-muta'adi bi harf min al-jar letter, and al-wasfi arrangement pattern. In idiomatic expressions translation, researchers use idiom expression translation strategies that is using similar meaning and form, and using similar meaning but dissimilar form.